2011
DOI: 10.1111/j.1365-2699.2011.02493.x
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary range dynamics of ecologically divergent species (Edraianthus serpyllifolius and E. tenuifolius, Campanulaceae) within the Balkan refugium

Abstract: Aim We investigated Quaternary range dynamics of two closely related but ecologically divergent species (cold-tolerant Edraianthus serpyllifolius and thermophilic Edraianthus tenuifolius) with overlapping distribution ranges endemic to the western Balkan Peninsula, an important yet understudied Pleistocene refugium. Our aims were: to test predictions of the 'refugia-withinrefugia' model of strong genetic subdivisions due to population isolation in separate refugia; to explore whether two ecologically divergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
86
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 71 publications
(151 reference statements)
11
86
3
2
Order By: Relevance
“…On the other hand, multiple Pleistocene refugia have been suggested for several species in the western Balkan Peninsula (e.g. Surina et al 2011) and the present three disjunct distribution areas might have been a result of vicariance in the Pleistocene. Whereas the sequence data are inconclusive regarding the relationships among the three population groups, the AFLP NeighbourNet shows that population 6 is nested within populations 1-4 from the Julian Alps, whereas the Sava valley populations (7-9) are separated by several shared splits (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, multiple Pleistocene refugia have been suggested for several species in the western Balkan Peninsula (e.g. Surina et al 2011) and the present three disjunct distribution areas might have been a result of vicariance in the Pleistocene. Whereas the sequence data are inconclusive regarding the relationships among the three population groups, the AFLP NeighbourNet shows that population 6 is nested within populations 1-4 from the Julian Alps, whereas the Sava valley populations (7-9) are separated by several shared splits (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary contacts between taxa or their lineages were most probably triggered by their range expansions and contractions during the Pleistocene (inter)glacial periods (e.g. Surina et al, 2011;Alarc on et al, 2012).…”
Section: Aflps Help Disentangle the Evolution And Biogeography Of Cyamentioning
confidence: 99%
“…A. DC. (Surina et al 2011), and Cardamine maritima DC. (Kučera et al 2008) showed a greater or lesser phylogeographical or taxonomical split in the area of the Neretva River Valley, such a split was not confi rmed here.…”
Section: Phenolic Compoundsmentioning
confidence: 99%